На что можно указать пальцем? Фрейм, практика, вещь и кое-что еще - Корбут, Андрей (Russian Sociological Review, 2011)
In the paper an attempt is made to view some of the most fruitful approaches to defining a sociology’s subject. It is argued that something becomes a sociology’s subject only inasmuch as it can be pointed to with a finger. Pointing with a finger is viewed as a research procedure referring to a concrete ways of organization and production of the social order phenomena. The main object of the critique here is the three approaches to defining sociology’s subject: frame analysis, theory of practices and sociology of things, which try to distinguish an observable features of social situations as something that participants must assign a meaning to. The alternative is to view social order phenomena as through and through local, accountable, competent, reproducible concerted sequences of action those accomplishment provide the participants with an observable and understandable features of the current situation of activity.